THE RECEPTION OF THE CLASSICS: DIALOGUES BETWEEN FELLINI AND PETRONIO - Aquati, Claudio [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
In this study, we're going to work first with the idea that we have, toward to the Latin novel, a broad, complex and important field of research which shows a large and varied material of study related to its dialogue with works of art from various periods, from antiquity until today. Next, we're going to discuss the evident and declared intertextuality between Fellini-satyricon and Satyrica, by Petronius. We understand that, on the one hand, if Fellini does not intent to establish a fidelity by a direct and simple translation of Petronius' work, and, on the other hand, if this director does not seek in Petronius' novel only reasons for the production of his movie, Fellini will have understood it as an intelligent background in order to connect an intense fantasy through which-with the representation of a very lively society full of heterogeneous elements (in actions, in feelings, in ethnic differences) that he takes from the novel-he discusses modern society in which the same human imperfections and contradictions remain, which would be far from being extinguished.
Keywords: Fellini; Fellini-satyricon; Petronius; Satyrica